Facebook, Twitter, and Blogs: The Adoption and Utilization of Social Media in Nonprofit Human Service Organizations. Issue 1 (1st January 2017) - Young, Jimmy A.
ABSTRACT: The following study examined how and why nonprofit human service organizations (HSOs) are using social media. Utilizing a cross-sectional survey design, HSOs answered questions that illustrate the adoption and utilization of social media across five dimensions: reasons for using social media, social media practices, frequency, general satisfaction, and future plans. Results indicate that HSOs are generally satisfied with social media, use it primarily to promote their organization and services, and despite limited resources, organizations plan to continue to use social media in the future. A discussion of the findings is given along with implications for future research and practice.